IMPROVING THE QUALITY OF TECHNOLOGY AND INFORMATION BASED LEARNING FOR TEACHERS AT SOUTH JAKARTA LEARNING INSTITUTIONS - Miftahul Farid Mochamad Ahyar; Ayi Ahmad Maulana Yusup; Fitri Senny Hapsari (Universitas PGRI Sumatera Barat, 2023)
Both formal and informal education systems have made extensive use of technology and information-based learning. Naturally, the standard must be raised in tutoring facilities, which serve as learning environments for kids who require more education than what is provided in the classroom. Digital literacy based on technology and information should be given more attention in response to world events that have been dominated by digitalization, including the world of education, in order to improve the quality of learning. A greater focus is required through training and socialization on the theme of improving the quality of technology-based and information-based learning for teachers at the GAMA UI tutoring institute Pondok Labu as an activity partner located in the south Jakarta area. This is because the lack of flying hours from teachers at tutoring institutions that are dominated by students raises problems in implementing technology and information-based learning.